Pengembangan Buku Cerita Bergambar Berbasis Pendidikan Lingkungan Hidup untuk Sekolah Dasar - Yuliza, Maryani; Alpusari, Mahmud; Zufriady, Zufriady (Indonesian Research Journal on Education, 2022)
The researchis to develop environmental education-based picture storybooks for elementary schools and to find out the feasibility of picture storybooks. This research uses Research and Development (R&D) using the ADDIE models (Analisys, Design, Development, Implementation and Evalution). The data collection technique used is to use questionnaires, interviews and trials. The feasibility of environmental education-based picture storybooks is derived from the results of validation and limited trials. Validation is done by media, material and language experts. The results showed that expert validation of media, materials and language was highly valid.The trial used in this study was a limited trial to 6 students andgot a response that was categorized as very feasible. The results of this development study show that environmental education-based picture storybooks for elementary schools are very feasible to use.